2013
DOI: 10.3109/01443615.2012.738717
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of gynaecological malignancies at the University of Ilorin Teaching Hospital, Ilorin, Nigeria

Abstract: Gynaecological malignancies contribute to the global burden of diseases and are of public health interest. The objective of this study was to determine the pattern of distribution of gynaecological malignancies seen between 1 January 2002 and 31 December 2006, at the University of Ilorin Teaching Hospital, Ilorin, Nigeria. It was a retrospective descriptive study. A total of 166 cases of gynaecological malignancies were encountered, cervical cancer was the most common (59.6%). This was followed by ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 11 publications
5
16
1
Order By: Relevance
“…(p=0.001) Cervical cancer accounted for majority (60.2%) of the female genital cancers in this study. This is consistent with results from similar studies in Abakaliki (60.6%), Ilorin (59.6%) and Benin (62.9%) (8,9,10). It is however slightly higher than the reports from Kano (48.6%) but lower than Abuja (65.5%), Jos (74.9%) and Zaria (77.0%).…”
Section: Introductionsupporting
confidence: 93%
“…(p=0.001) Cervical cancer accounted for majority (60.2%) of the female genital cancers in this study. This is consistent with results from similar studies in Abakaliki (60.6%), Ilorin (59.6%) and Benin (62.9%) (8,9,10). It is however slightly higher than the reports from Kano (48.6%) but lower than Abuja (65.5%), Jos (74.9%) and Zaria (77.0%).…”
Section: Introductionsupporting
confidence: 93%
“…Surgery was the first step in the management of the most cases in the current study as the authors demonstrated that 50% of the most common two types of primary gynaecologic cancers; both uterine and ovarian are located in early stages of the disease; Stages I and II, while 50% of cervical and vulvar cancers presented in Stage I of the disease ( Table 3). Contrary to what has been stated above, many studies that originated from developing countries reported cervical cancer to be the most common type of genital malignancies [24][25][26][27], which found to have the highest incidence and mortality rate worldwide [11], but not surprising to know that cervical cancer is a preventable disease due to valid and widespread screening programs, long-lasting preinvasive period, and effective treatment as applied in the patients in this study being mostly presented and diagnosed in the early stages were 50% in Stage I disease, but all in all the high incidence worldwide reflecting the poor screening programs for early detection of cases in the premalignant stages. In contrast, the existence of widespread cervical screening programs in the developed world tremendously reduced the burden of cervical malignancy.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, Black women diagnosed with EOC are diagnosed at more advanced stages, as have been shown in larger SEER data (11,22). Nigerian women had a lower proportion of EOC cases, an observation previously published in a single institutional study (23)(24)(25). Further, differences in reported ovarian histotypes across Nigeria potentially suggest different culturalhealth behavioral practices and thus exposures that may influence risk of ovarian cancer histologic development.…”
Section: Discussionmentioning
confidence: 66%